La solución de un problema matemático no convencional por estudiantes universitarios - Hernández-Morales, Juan Arturo; Castañeda-Alonso, Apolo; González-Polo, Rosa Isela (Revista Científica, 2019)
In traditional education, mathematical problems are usually considered as a way of applying concepts or exercising procedures, however, in this research it was proposed to rethink this approach by introducing other types of problems to the mathematics class to encourage new tasks and reflections. The article reports the implementation of a non-conventional mathematical problem with the objective of identifying and analyzing the arguments of university students. This type of problems is characterized by open slogans and admit various procedures for their solution. To analyze the students' productions, the argumentative model of Toulmin was used, which allowed to identify the structure of the reasoning, from the data to the conclusion. The results showed that some students faced difficulties because the information in the problem is not completely explicit and they argued the lack of data or errors in its writing. In the case of those students who could solve it, it was observed that they were widely involved with the problem, they analyzed and presented different interpretations, the discussion of variables and their relationships was encouraged, mathematical knowledge was used to justify their procedures.